Communication, Information and Education Iron Supplementation and Hemoglobin - Indrayoni, Putu; Megayanti, Sri Dewi (Jurnal Abdimas ITEKES, 2021)
nemia in young women can cause decreased concentration in learning, lack of enthusiasm in activities, decreased memory and decreased learning ability at school. National prevalence of anemia in Indonesia reaches 21.7%, with anemia sufferers aged 5-14 years of 26.4% and 18.4% of patients aged 15-24 years with the highest prevalence in women. Iron nutrition anemia in adolescents becomes dangerous if not handled properly, especially in preparation for pregnancy and childbirth when they are adults. The solution related to the problem of anemia in adolescents can be in the form of providing a refresher on knowledge about good nutritional intake for students providing iron supplementation and checking Hb levels in female students. To determine the change in knowledge in adolescent students, a pre and post test was conducted using a knowledge questionnaire about the importance of iron supplementation followed by measuring the status of the risk of anemia. The data shows that the pretest results are 71.43% with sufficient knowledge and the post test shows that 100% of students have good knowledge. From the results of Hb examination, it was found that the average Hb value of female adolescent students was 12.5 gr / dl with the lowest value 11.2 gr / dl and the highest value 14.7 gr / dl. From these data it can be seen that the provision of KIE FE supplementation is useful for students of SMK Kesehatan Panca Atma Jaya Klungkung.